Kajian keselesaan terma di penginapan pelajar Universiti Sains Malaysia - Mohd Sari, Kamarul Aini (2003)
Thermal comfort is defined in ASHRAE Standard 55-1992[2) as being 'The condition of mind that expresses satisfaction with the thermal environment'. The thermal comfort study has been done in five desasiswa at Universiti Sains Malaysia main campus which involved undergraduate and postgraduate student. The problem of introduction is related with issue uncomfortable student of the space provided. The main objective of the study is to know thermal comfort level of the student in living space according to their vote based on ASHRAE seven thermal sensational scale. The human body normally rejects heat to the environment using evaporative cooling (sweating) and the heat transfer mechanism of radiation, convection and conduction. The field method is applied ini this study which involved social survey, questionnaire and measurement on environment parameters. Three main faktor that control thermal comfort are environment, individual and others. The combination of passive and active ventilation in a space influence the thermal comfort. In addition to it's thermal climate, the air quality of each indoor environment affects the sense of comfort. In order to decrease health hazard and move odour , a control of ventilation should be stressed.